'He's One of Ours': A Case Study of a Campus Response to Crisis. (22nd May 2015) - Jenkins, Shannon; Goodman, Michael
<x xml:space="preserve">Abstract</x> Early on Friday, 19 April 2013, officials at the University of Massachusetts Dartmouth learned that one of the Boston Marathon bombing suspects was an enrolled student. That morning, the entire campus was transformed into both a crime scene and a potential target for an act of domestic terrorism. This article examines the campus response to this crisis, based on interviews with campus officials and a review of a task force report produced to review the campus response. This case study speaks to three important issues in the crisis management literature. Having a crisis plan helps (1), but testing of these plans is critical for an effective response (2). Furthermore, the plan must allow for real‐time decision making that is both centralized and decentralized (3).